Analysis of the municipal management of the monumental area of the district of Ancón (2019-2022), Lima-Peru - Hernandez Quesquen, Janet (2025)
Municipal management is comprised of complex actions and responsibilities that seek the development and well-being of the local community. Under this premise, the fulfillment of objectives and goals established in the municipal government plan is sought. This article studies the municipal administration of the Ancon district during the period 2019-2022 with the objective of carrying out the descriptive and analytical analysis of the management of the district's cultural heritage. This research demonstrates the allocation of budgets to fulfill each objective, but the health crisis experienced in the world, the political situation of the country, the lack of suitable professionals and the lack of an adequate action plan to help prioritize social issues by subtracting relevance. to the once aristocratic monumental area and the vast pre-Hispanic necropolis of Ancon. In summary, the municipal management of Ancon (2019-2022) regarding cultural and heritage issues was politically inefficient.